Anticaries activity of mangiferin isolated from Mangifera indica leaves in Vietnam - Quang, Ngo Van; Luong, Dang Vu; Xuan, Do Thanh; Thu, Quach Minh; Tai, Nguyen Tien; Tam, Nguyen Quang; Thu Thuy, Thanh Thi; Mai Phuong, Nguyen Thi (Vietnam Journal of Chemistry, 2017)
Mangiferin (1) was isolated from Vietnamese Mangifera indica leaves. Its antimicrobial activities against the oral bacterium Streptococcus mutans GS-5 were evaluated in terms of inhibition of acid production and biofilm formation. The obtained results indicated that mangiferin at the concentration of 0.5 mM clearly inhibited acid production by this organism with a final pH value of 5.2 compared to 3.9 of the control. The reduction in biofilm biomass was found up to 92 % when it was treated with 1.0 mM mangiferin. Thus, mangiferin possesses moderate anticaries activity against S. mutans GS-5. Keywords. Mangifera indica, mangiferin, Streptococcus mutans, anticaries activity.